Properties of foamed concrete with processed spent bleaching earth as partial cement replacement - Rokiah, Othman (2020)
The production of Portland cement leads to a significant amount of carbon dioxide (CO2) emitted from the calcination of limestone. Related to this, the construction industry stands to reduce CO2 emission by incorporating waste or industrial by-products as cement replacements that lead to making the concrete more environmentally green. The bleaching earth that used for decolouring during the palm oils refining process form a solid sludge called spent bleaching earth (SBE).The waste usually dumped in a landfill without any treatment. The SBE is generated in large quantity and it is becoming increasingly difficult to ignore the disposal of SBE when production of palm oil increased. Therefore, this research investigates the effect of Processed Spent Bleaching Earth (PSBE) as a partial cement replacement on the fresh properties, mechanical properties and durability properties of foamed concrete (FC). Processed Spent Bleaching Earth Foamed Concrete (PFC) is a mixture of cement paste with pre-foamed foam by using PSBE as partial cement replacement. The usage of PSBE will decrease the cement consumption, lesser the waste thrown at the landfill and reduce the environmental pollution issue. The first objective of the study is to determine the optimum percentage of PSBE as a partial cement replacement. The experiments involved six different types of mixtures with partial replacement of cement by 0%,10%,20%,30%,40% and 50% of PSBE were conducted. Mix containing 30% PSBE specimen exhibited 56% higher compressive strength, 40% higher flexural strength and 58% higher modulus of elasticity as compared to control FC. The second objective of the study is to investigate the effect of different curing regimessuch as water curing, air curing, initial water for 7days and follow by air curing, natural weather and initial water for 7days and follow by natural weather on the mechanical properties of FC containing PSBE. The specimen cured in initial water for 7days and follow by natural weather exhibited excellent results, while specimen cured in air curing provides lowest results compared to others. The third objective of the study is to investigate the durability properties of FC containing PSBE. It is interesting to note that 30% PSBE specimen exhibited better durability with 52% lower water absorption, 45% lower porosity and 60% lower carbonation depth as compared to control FC. The 77% lower charge passes than FC shown the great resistance to chloride ion penetration with low moderate permeability. At the end of the immersion period in hydrochloric acid, the 30%PSBE specimen exhibit better durability than control specimen FC with 0.25% loss in mass and 5.42% loss in strength in 5% acid solution for 1800 hour. Similarly, after immersion in sodium sulphate, the 30%PSBE specimen exhibit better durability than control specimen FC with 1.32% change in mass, 0.98% change in expansion and 7.5% loss in strength in the 5% sodium sulphate after 52 weeks. The microstructure study has confirmed that inclusion of PSBE in FC is known to improve the internal structure of PFC to be denser than control FC specimen with the visible image of crowded tiny of cotton shaped (CSH) and few hexagonal plates (CH) contributing to enhanced strength and durability. Based on the regression analysis, the results show strong correlation between the selected independent variable and dependent variable due to the R2 value closer to one. Conclusively, the foamed concrete containing 30% PSBE as partial cement replacement fullfill the requirement for strength of structural bearing load which exhibits enhanced strength and durability than plain foamed concrete has the potential to be used in construction application.